The Cryptic Plastid of Euglena longa Defines a New Type of Nonphotosynthetic Plastid Organelle - Füssy, Zoltán; Záhonová, Kristína; Tomčala, Aleš; Krajčovič, Juraj; Yurchenko, Vyacheslav; Oborník, Miroslav; Eliáš, Marek (mSphere, 2020)
Most secondary nonphotosynthetic eukaryotes have retained residual plastids whose physiological role is often still unknown. One such example is Euglena longa, a close nonphotosynthetic relative of Euglena gracilis harboring a plastid organelle of enigmatic function. By mining transcriptome data from E. longa, we finally provide an overview of metabolic processes localized to its elusive plastid. The organelle plays no role in the biosynthesis of isoprenoid precursors and fatty acids and has a very limited repertoire of pathways concerning nitrogen-containing metabolites. In contrast, the synthesis of phospholipids and glycolipids has been preserved, curiously with the last step of sulfoquinovosyldiacylglycerol synthesis being catalyzed by the SqdX form of an enzyme so far known only from bacteria. Notably, we show that the E. longa plastid synthesizes tocopherols and a phylloquinone derivative, the first such report for nonphotosynthetic plastids studied so far. The most striking attribute of the organelle could be the presence of a linearized Calvin-Benson (CB) pathway, including RuBisCO yet lacking the gluconeogenetic part of the standard cycle, together with ferredoxin-NADP+ reductase (FNR) and the ferredoxin/thioredoxin system. We hypothesize that the ferredoxin/thioredoxin system activates the linear CB pathway in response to the redox status of the E. longa cell and speculate on the role of the pathway in keeping the redox balance of the cell. Altogether, the E. longa plastid defines a new class of relic plastids that is drastically different from the best-studied organelle of this category, the apicoplast.IMPORTANCE Colorless plastids incapable of photosynthesis evolved in many plant and algal groups, but what functions they perform is still unknown in many cases. Here, we study the elusive plastid of Euglena longa, a nonphotosynthetic cousin of the familiar green flagellate Euglena gracilis We document an unprecedented combination of metabolic functions that the E. longa plastid exhibits in comparison with previously characterized nonphotosynthetic plastids. For example, and truly surprisingly, it has retained the synthesis of tocopherols (vitamin E) and a phylloquinone (vitamin K) derivative. In addition, we offer a possible solution of the long-standing conundrum of the presence of the CO2-fixing enzyme RuBisCO in E. longa Our work provides a detailed account on a unique variant of relic plastids, the first among nonphotosynthetic plastids that evolved by secondary endosymbiosis from a green algal ancestor, and suggests that it has persisted for reasons not previously considered in relation to nonphotosynthetic plastids.
Keywords: Plastids; molekulární evoluce; Phylogeny; transkriptom; Photosynthesis; Transcriptome; fylogeneze; plastidy; Euglena longa; Evolution, Molecular; fotosyntéza